2015
DOI: 10.1016/j.jns.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of gait ataxia by accelerometers

Abstract: Correspondence to Hidenao Sasaki, h-isasak@med.hokudai.ac.jp Although there are various types of biomarkers such as molecular markers and imaging markers, an appropriate maker for neurodegenerative disease has not been identified. Thus, we use clinical evaluation scales. However, it is important to identify an appropriate biomarker in order to evaluate the efficiency of a given clinical trial.Here, we performed gait analyses in patients with pure cerebellar type spinocerebellar degeneration (SCD) and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 14 publications
(21 reference statements)
3
38
1
Order By: Relevance
“…Few reports have yet been performed using wearable gait sensors in patients with ataxia . Among these, Shirai et al . studied 25 degenerative cerebellar ataxia patients using the Gait‐Kun system and found that step‐width (medial–lateral) variation was prominent, in accord with previous studies .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Few reports have yet been performed using wearable gait sensors in patients with ataxia . Among these, Shirai et al . studied 25 degenerative cerebellar ataxia patients using the Gait‐Kun system and found that step‐width (medial–lateral) variation was prominent, in accord with previous studies .…”
Section: Discussionsupporting
confidence: 60%
“…To date, this technology has been applied in neurologic conditions including head trauma, Parkinson's disease, hemiplegia, paraplegia–spasticity, and distal neuropathy, in order to analyze gait more precisely. In contrast, only a few reports are available using wearable gait sensors in patients with ataxia including one study by Shirai et al . They studied 25 patients with SCD, showing that step‐width (medial–lateral) variation was prominent in their patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated each lateral displacement by double integration with high-pass filtering of the resulting acceleration from a tilt-compensated sensor donned at the head, trunk, and pelvis, respectively. 33,34 The amount a crewmember swayed from side to side during tandem walking was measured by the area under the ML displacement curve using integration.…”
Section: Methodsmentioning
confidence: 99%
“…Human gait is a highly complicated and integrated bipedal locomotion activity that can be characterized by multivariate data; therefore, simpler and more comprehensive methods are needed for the interpretation of such data. Several of the gait parameters obtained using a triaxial accelerometer have been proven to be useful for the clinical assessment of ataxia in SCA and MSA-C patients [10, 11]; however, a method for the integrated analysis of various gait parameters directly reflecting ataxic gait has not yet been developed. Principal component analysis (PCA) is a statistical approach used to process complicated multivariate data.…”
Section: Introductionmentioning
confidence: 99%